The Effectiveness of Botvin’s Life Skills Training Model in Reducing Juvenile Delinquency Influenced by Environmental Factors among Junior High School Students - Nabilla, Rista; Laily, Nadhirotul (Universitas Negeri Padang, 2025)
This study aims to examine the effectiveness of Botvin’s Life Skills Training (LST) Model in reducing juvenile delinquency influenced by environmental factors among students at UPT SMPN X Gresik. The main problems identified include smoking, skipping classes, fighting, and violating school rules—behaviors largely shaped by peer pressure and lack of parental supervision. The intervention involved three sessions of Life Skills Training focusing on personal self-management, social skills, and refusal skills. This research used a pre-test and post-test design with the Juvenile Delinquency Scale adapted from Trie Utami Lestari (2022). Data were analyzed descriptively using percentage scores. The results revealed a substantial decrease in delinquent behavior, with scores declining from 942 (80%, high category) to 226 (19%, low category). These findings indicate that the Botvin Life Skills Training Model effectively reduces juvenile delinquency driven by environmental factors by enhancing students’ self-control, decision-making, and social competence. The study provides practical implications for schools to integrate life skills programs as preventive and developmental approaches in character education.